A PRELIMINARY STUDY ON TRUSTWORTHINESS FRAMEWORK FOR TRADITIONAL MALAY MEDICINE DATA RETRIEVAL - Basar, Muhammad Alif; Abu Seman, Muhamad Sadry; Mohd Shafri, Mohd Affendi; Mohamed, Farahidah (Asian Journal Of Medical Technology, 2024)
Traditional Malay Medicine data retrieval may have the potential to contribute to the COVID-19 pandemic response. However, trustworthiness issues may hinder for medical professionals from accepting its formulations. This paper presents a preliminary study of trustworthiness frameworks in PubMed and IEEE related to Covid-19. The study examined three aspects of Traditional Malay Medicine data retrieval; (1) Manuscript Original Verification, (2) Author Profiling method, and (3) in-database module trust framework. Three relevance frameworks are selected based on each focus aspect. We proposed a scoring system that emphasizes on the authenticity of the source or provider of the manuscript. We suggested a replicability evaluation of the authors' formulation to enhance their credibility. In-database module trust framework covered by a set of dynamic rules. It offers reliable ways to implement trustworthiness in the database. This review will help establish standards and guidelines for evaluating Traditional Malay Medicine Trustworthiness. Thus, inspire current researchers to explore Traditional Malay Medicine's role in response to future pandemics.